Application of lactobacillus species in the development of probiotic poultry feed as an alternative to antibiotic growth promoters - Sharmin, Saifa (BRAC University, 2018)
This dissertation is submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology 2017.